(untitled) (African Disability Rights Yearbook, 2021)
World Health Organisation estimates place the number of disabled persons in Nigeria at approximately 20 per cent of the country’s population. This article uses the 1999 Nigerian Constitution, as amended, as the main pivot for discussion with respect to ‘disabled people’. The provisions of the Nigerian Constitution relating to non-discrimination are ambivalent with respect to disabled peoples’ rights. In spite of significant strides towards constitutional amendments in Nigeria, state actors, as a matter of self-interest, have continued to overlook the alienation of disabled people from legal, socio-economic and political processes. An analysis of the provisions of the Constitution on non-discrimination reveals a contradiction in law that outwardly embraces equality but inwardly effectuates inequality in relation to disabled people. Nonetheless, it is argued that, despite the inherent contradictory constitutional provision, the possibility of reading disability into the non-discrimination clause is not entirely lost. It is contended that the law should be more inclusive and protective of the needs and aspirations of underprivileged and disadvantaged members of society.